أثر برنامج تعليمي مقترح على المستوى المهاري في بعض الرياضات لدى تلاميذ الطور الابتدائي - دودو, بلقاسم; ناجم, نبيل; توفيق, قعقاع (دفـاتر المـــــــــــخبـر, 2018)
ملخص : تهدف هذه الدراسة إلى التعرف على أثر البرنامج التعليمي المقترح على المستوى القني والمهاري لدى تلاميذ الطور الابتدائي، ومن أجل تحقيق ذلك قام الباحثون باستخدام المنهج التجريبي الذي يعد من أكثر الوسائل كفاية في الوصول الى معرفة موثوق بها، وقد تضمنت عينة الدراسة عينتين الاولى تمثلت في تلاميذ الطور الابتدائي وتحديدا السنة الرابعة ابتدائي حيث بلغ عددهم 60 تلميذا، أما العينة الثانية فتمثلت في معلمي المرحلة الابتدائية وبلغ عددهم 20 معلما. وقد اختيرت العينتين بالطريقة العمدية، ولدراسة تأثير البرنامج التعليمي المقترح تم استخدام مجموعة من الاختبارات تمثلت في (اختبار الجري الارتجاجي 10×05، العدو 50 متر، اختبار التوافق، تنطيط الكرة حول الملعب)، وتوصل الباحثون الى إن البرنامج التعليمي المقترح يساهم بشكل ايجابي في تحسين المستوى التقني والمهاري لدى تلاميذ الطور الابتدائي في كل من نشاط الجري السريع وكرة اليد. Abstract : This study aims to identify the impact of the proposed program of education level skill and skills among students of primary phase, in order to achieve this, the researchers then use the experimental method which is one of More means the adequacy of access to reliable knowledge, and study sample included the first two samples was the pupils of primary phase, specifically the fourth year of primary schooling where numbered 60 students, while the second sample were: the primary teachers and numbered 20 teachers, were selected samples purposively, to study the effect of the proposed educational program was used set of tests was the (test run vibratory 10 × 05, the enemy 50 meters, compatibility testing, bouncing the ball around the field), the researchers concluded that the proposed educational program contributes positively to the improvement of technical skill level among students phase in each of the primary to run fast activity and handball